The Description of the Body Image of Adolescent Girls During Puberty - Fauzania, Syifa Nurul; Solehati, Tetti; Hidayati, Nur Oktavia (GLOBAL HEALTH SCIENCE GROUP, 2024)
Physical changes during puberty are very rapid and are not balanced with psychological changes, which can cause adolescents to pay more attention to their body shape and appearance. If adolescents are unable to accept their body image, it can affect their daily behaviors such as self-confidence, eating patterns, and dietary behavior. This study aims to determine the description of the body image of adolescent girls during puberty at SDN Cingcin 01. This research design is quantitative descriptive. This study used a total sampling technique with a sample size of 55 female students at SDN Cingcin 01 who had reached puberty. Total sampling was used in this study because the population is less than 100 people. Data was collected using the Multidimensional Body Self Relations Questionnaire-Appearance Scale (MBSRQ-AS) to measure the body image with validity test results ranging from 0.438-0.795, and the reliability test results 0.922. Univariate analysis was carried out using descriptive statistics. The results showed that 28 respondents (50.9%) were in the negative body image category. Based on the dimensions, respondents had negative perceptions of appearance evaluation (56.4%) and overweight preoccupation (52.7%), positive perceptions of appearance orientation (56.4%), body area satisfaction (58.2%), and self-classified weight (78.2%). In conclusion, half of the respondents had a negative body image. It is recommended for schools to do health education to improve the body image of their female students.